Nikon D600 for dummies - King, Julie Adair (John Wiley & Sons, 2013)
The Nikon D600 is a professional-level full-frame sensor that is sure to attract an audience of DSLR newcomers and pros. This friendly-and-thorough full-color guide shows you how to get a firm grasp on this powerful camera and helps you to ultimately get better photos.